Our new baby - Kueffner, Sue.; Stott, Dorothy M. (Pleasantville, NY : Reader$1 (Bs Digest Children$1 (Bs Books,s, 1999)
A sister initially resents but then comes to love her new baby brother.
Includes gold star reward stickers.
"Preschool-grade 1"--cover.
Keywords: Babies -- Fiction; Brothers and sisters -- Fiction; Stories in rhyme